2021
DOI: 10.1002/jgm.3326
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR‐181a and miR‐223 expression with the potential value of biomarkers for the diagnosis of systemic lupus erythematosus and predicting lupus nephritis

Abstract: Background: MicroRNAs (miRNAs) contribute to the development and progression of systemic lupus erythematosus (SLE) by affecting a wide range of targeted genes and facilitating the development of lupus nephritis (LN). The present study aimed to analyze the serum expression of miR-181a and miR-223 in SLE patients and to assess whether they could serve as novel biomarkers for SLE diagnosis and to distinguish LN. Methods: The study included 70 control subjects and 116 patients with SLE (67 non-LN and 49 LN groups)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…A growing number of studies have investigated the role of microRNAs (miRNAs) as putative epigenetic biomarkers in LN. These short single-stranded RNA molecules have been implicated in multiple regulatory events of gene expression [ 43 ], and differential levels of different miRNAs, including miRNA-21, miRNA-146a, miRNA-150, miRNA-155, miRNA-181a, miRNA-223, and miRNA-423, have been linked to kidney involvement in patients with SLE [ 44 , 45 , 46 , 47 ]. In particular miRNA-21 displayed a satisfactory ability to distinguish between patients with active LN compared with a group of patients with either inactive LN or non-renal SLE (AUC = 0.89; p < 0.001) [ 45 ], as well as patients with LN from healthy controls (AUC = 0.91; sens.…”
Section: Resultsmentioning
confidence: 99%
“…A growing number of studies have investigated the role of microRNAs (miRNAs) as putative epigenetic biomarkers in LN. These short single-stranded RNA molecules have been implicated in multiple regulatory events of gene expression [ 43 ], and differential levels of different miRNAs, including miRNA-21, miRNA-146a, miRNA-150, miRNA-155, miRNA-181a, miRNA-223, and miRNA-423, have been linked to kidney involvement in patients with SLE [ 44 , 45 , 46 , 47 ]. In particular miRNA-21 displayed a satisfactory ability to distinguish between patients with active LN compared with a group of patients with either inactive LN or non-renal SLE (AUC = 0.89; p < 0.001) [ 45 ], as well as patients with LN from healthy controls (AUC = 0.91; sens.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies have demonstrated that miRNAs are crucial in diagnosing, monitoring disease activity, prognosticating, and treating LN in clinical settings. MiR-181a and miR-223 expression analysis in combination may be useful for diagnosing SLE and predicting LN in Egyptians (Xu et al, 2018;Abdul-Maksoud et al (2021). demonstrated, for the first time, that miR-181a has a significant positive correlation with SLEDAI, proteinuria, blood urea, and serum creatinine (p < 0.001), whereas miR-223 downregulation is significantly negatively correlated with SLEDAI, proteinuria, blood urea, and serum creatinine (Abdul-Maksoud et al, 2021).…”
Section: Micrornas In Lupus Nephritismentioning
confidence: 94%
“…Numerous reviews and preclinical and clinical studies have established and discussed the critical roles of various miRNAs in the development, prognosis, and therapies of LN (Dominguez-Gutierrez et al, 2014;Habibi et al, 2016;Li et al, 2017;Trinh et al, 2017;Zhu et al, 2017;Xu et al, 2018;Ye et al, 2018;Feng et al, 2019;Liu et al, 2019;Qi et al, 2020;Shao et al, 2020;Sun et al, 2020;Abdul-Maksoud et al, 2021;Du et al, 2021;Perez-Hernandez et al, 2021;So et al, 2021;Xu et al, 2021;Zhang et al, 2021). There has been much research and review on the role of miRNAs in LN over the last decade, and several wellknown miRNAs have been linked to the development and progression of LN (Table 1).…”
Section: Micrornas In Lupus Nephritismentioning
confidence: 99%
See 1 more Smart Citation
“…Serum hsa-miR-766-3p regulates the PI3K-AKT-mTOR pathway in SLE patients and participates in kidney injury ( 68 ). miR-181a and miR-223 can be used as serum biomarkers to diagnose SLE and predict LN in Egyptians ( 69 ). The high expression of miR-485-5p in the serum of SLE and LN patients is positively correlated with the glomerular filtration rate and serum creatinine, proteinuria, and inflammatory cytokine levels ( 70 ).…”
Section: Candidate Rnas As Sle Biomarkersmentioning
confidence: 99%